Numerical Simulations for Two Way Shape-Memory-Alloy MEMS 3D Tunable Inductors (ELEKTRIKA- Journal of Electrical Engineering, 2021)
This paper presents numerical simulations for microelectromechanical systems (MEMS) tunable 3D inductor using two-way shape-memory-alloy (SMA). MEMS inductors are significant to develop the small scale, lightweight and high-performance wireless communications technologies. The inductance value often varied depending on its application. Hence in this work, a 3D tunable inductor is developed using two-way SMA actuation. A numerical simulation is performed by using COMSOL Multiphysics software to evaluate the temperature of the SMA inductor during Joule heating and the inductance values based on its actuation heights. The results of the numerical simulations show that when a 0.4 A DC current is supplied, the temperature at the spiral coil of the 3D tunable inductor reaches 67.86 °C. Meanwhile the inductance value of the 3D tunable inductor is lower when the height of the actuation is increased. When the height of the 3D tunable inductor is at 6mm and 3.6mm, the inductance value is 0.97nH to 1.56nH respectively. It is expected that the results if work would encourage developments of 3D tunable inductors in wireless displacement sensor.